2007
DOI: 10.1002/ptr.2161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary red clover on blood factors and cardiovascular fatty streak formation in hypercholesterolemic rabbits

Abstract: Phytoestrogens with a biological activity like estradiol are naturally found in many plants. This study was designed to investigate the effect of red clover, a phytoestrogen-rich member of the legume family (Trifolium pratense) on the development of atherosclerosis in male hyperlipidemic rabbits. Twenty rabbits were semi-randomly distributed into four groups of five each. Two groups received either normal diet or normal diet supplemented with red clover. Two other groups received similar diets to both of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…Xanthophylls and compounds of a similar mode of action reduce lipoxidase activity and decrease blood cholesterol content of animals and humans (27). The Pakistan studies on rabbits showed elevated concentration of the HDL fraction of cholesterol and lowered fat deposits clogging the arteries (2). Substantial reduction of total cholesterol and the LDL fraction in the blood of rabbits fed alfalfa concentrate supplement was reported by Khaleel et al (16).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Xanthophylls and compounds of a similar mode of action reduce lipoxidase activity and decrease blood cholesterol content of animals and humans (27). The Pakistan studies on rabbits showed elevated concentration of the HDL fraction of cholesterol and lowered fat deposits clogging the arteries (2). Substantial reduction of total cholesterol and the LDL fraction in the blood of rabbits fed alfalfa concentrate supplement was reported by Khaleel et al (16).…”
Section: Discussionmentioning
confidence: 88%
“…The functional competence and metabolic profile of body fluids and tissues can change in response to feed additives used. Reviews published recently have highlighted herbal plants as dietary supplements (26), among them alfalfa preparation (2,3). Recent studies have underlined its effectiveness on sheep (21,29), turkeys (19), laying hens (12), broiler chickens (8), and finally, pigs (14,15,22), where low alfalfa protein concentrate (APC) supplementation in the 2% -3% range caused higher weight gains and better feed conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to this critical conclusion, a growing number of reports suggest the considerable medicinal value of red clover, e.g., the improvement of postmenopausal depressive and anxiety symptoms (Lipovac et al, 2010). Moreover, other beneficial activities of substances and extracts of T. pratense, such as cardiovascular disease-preventive effects, were also (Asgary et al, 2007). The physiological actions and biological properties of clover species other than T. pratense have not been well described; however, some evidence confirming a considerable therapeutic potential of various clovers is available (Renda et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Alfalfa has an extremely high nutritive value; it includes vitamins A, B1, B6, B12, C, D, E, and K, niacin, pantothenic acid, biotin, folic acid, minerals, protein, and benefi cial saponins [5,6]. Previous studies showed that adding alfalfa seed in human diet reduced triglycerides and LDL, improved HDL levels, and decreased blood glucose [7,8]. Therefore, alfalfa leaves are traditionally used in South Africa as an eff ective treatment for diabetes [9,10].…”
Section: Introductionmentioning
confidence: 99%